Edge intelligence empowered internet of vehicles: concept, framework, issues, implementation, and prospect - Kai JIANG; Yue CAO; Huan ZHOU; Xuefeng REN; Yongdong ZHU; Hai LIN (物联网学报)
As an emerging inter discipline field, edge intelligence pushes AI to the side close to the traffic data source.Edge intelligence makes use of the computing power, storage resources, and perception ability of edge to provide a more intelligent and efficient resource allocation and processing mechanism while providing a real-time response, intelligent decision-making and network autonomy, realizing the critical leap for internet of vehicles from access “pipelining” to the intelligent enabling platform of information.However, the successful implementation of edge intelligence in internet of vehicles is still in its infancy, and there exists a demand for a comprehensive survey in this young field from a broader perspective.Based on this context of internet of vehicles, the background, concepts and key technologies of edge intelligence were introduced.Then, a holistic overview of service types based on internet of vehicles was taken, and the entire processes of model training and inference in edge intelligence were elaborated.Finally, to promote the potential research directions, the key open challenges of edge intelligence in the internet of vehicles were analyzed, and the coping strategies were discussed.